Shining a Light on the Mysteries of State : The Origins of Fiscal Transparency in Western Europe - Irwin, Timothy (Washington, D.C. : International Monetary Fund, 2013)
The extent of fiscal transparency in Western Europe has varied over the centuries. Although ancient Greek, Roman, and medieval governments were sometimes open about their finances, the absolute monarchies of the 1600s and 1700s shrouded them in mystery. Factors that have encouraged transparency include (i) the sharing of political power and rulers' need to persuade creditors to lend and taxpayers' representatives to approve new taxes; (ii) the spread of technological innovations that reduce the costs of storing and transmitting information; and (iii) the acceptance of political theories that emphasize accountable government and public discussion of government policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet